Electric field calculation of high-voltage direct current transmission lines - Троценко, Євгеній Олександрович (Technology audit and production reserves, 2015)
It is adapted charges equivalent method for calculating the electrostatic field intensity under single-stranded and double-stranded bipolar DC transmission lines in the absence of corona wires on line in dry climates. Simple and noniterative calculation method required in order to engineer could assess whether not to exceed maximum permissible levels of the electrostatic field strength in DC power lines. As a result of research first obtained expressions that simplify engineering calculations of electrostatic field, taking into account the symmetry of the poles as the central axis supports of bipolar lines, and do not use iterative methods of payment. Development of methods for calculating electric field of direct current transmission lines is an important task, because in the near future is expected to increase the number of data transfers in the world, not only by building new, and as a result of the conversion of existing lines AC line DC.